2012
DOI: 10.1177/0192512111415983
|View full text |Cite
|
Sign up to set email alerts
|

Where does religion meet democracy? A comparative analysis of attitudes in Europe

Abstract: Starting from the growing importance of religion for politics, this article tests whether religion in Europe is connected with democratic attitudes. Analyzing and understanding such a relationship is essential for a better understanding of the prospects of present and future democratic consolidation. Our two-step approach aims to assess the variation and causal forces of democratic attitudes in Europe in the light of broader country-level factors and individual proclivities towards religion and politics. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…We examined whether and how religion at individual and national levels is related to democratic citizenship norms and political participation in a sample of predominantly-Christian democracies. Our results confirm, as expected, that individuals who attend religious services more frequently place much greater emphasis on citizenship duties and are somewhat more involved in political activities (see e.g., Denters et al 2007; Bolzendahl and Coffé 2009; Ben-Nun Bloom and Arikan 2012; Vlas and Gherghina 2012; Smidt 2013),…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We examined whether and how religion at individual and national levels is related to democratic citizenship norms and political participation in a sample of predominantly-Christian democracies. Our results confirm, as expected, that individuals who attend religious services more frequently place much greater emphasis on citizenship duties and are somewhat more involved in political activities (see e.g., Denters et al 2007; Bolzendahl and Coffé 2009; Ben-Nun Bloom and Arikan 2012; Vlas and Gherghina 2012; Smidt 2013),…”
Section: Discussionsupporting
confidence: 90%
“…Individual religiosity has been positively linked to certain aspects of citizenship including democratic values (Denters et al 2007; Bolzendahl and Coffé 2009; Ben-Nun Bloom and Arikan 2012; Vlas and Gherghina 2012; Smidt 2013), civic involvement (Ruiter and De Graaf 2006; Putnam and Campbell 2010; McAndrew and Voas 2013; Smidt 2013), and political participation including voting, party membership, and protest (Norris 2002; Driskell et al 2008; Norris and Inglehart 2011; Smidt 2013; Arikan and Ben-Nun Bloom 2019). The mechanisms explaining this connection are multiple and overlapping.…”
Section: Individual Religiosity and Democratic Citizenshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Arab Barometer, Kostenko et al (2016) for example demonstrated that democratic values in Arab countries are not linked to gender equality (Kostenko et al 2016;Rizzo et al 2007). Meanwhile, Vlas and Gherghina (2012), contest claims about Muslim patriarchy by showing that democratic and equality values are not linked to religion but rather to living in a patriarchal society.…”
Section: Lessons Learned From Comparative Values Researchmentioning
confidence: 99%
“…Others argue more explicitly that democracy is only possible in secular societies or at least in those with strong separation of religion and state. They consider that stable democracy in religiously divided societies is possible only if complicated power-sharing arrangements are present (Lijphart 1997;Kalyvas 1998;Brathwaite and Bramsen 2011;Vlas and Gherghina 2012). Overall, these positions implicitly reflect the taken-for-granted privatization of religion that characterized democratization in Europe, as well as the neat religion versus political divide that is taken for granted in IR scholarship.…”
Section: Religion Democracy and Democratizationmentioning
confidence: 99%